A study of Reiki therapy on unpleasant symptoms in children with cerebral palsy. (February 2022) - Love, Lamara; Anderson, Avery M.; von Sadovszky, Victoria; Kusiak, Julie; Ford, Jodi; Noritz, Garey
Abstract: Children with Cerebral Palsy (CP) commonly experience unpleasant symptoms such as pain, anger, and sadness. The purpose of this quasi-experimental study, guided by the Theory of Unpleasant Symptoms (TOUS), was to examine the practicality and impact of delivering Reiki Therapy (RT) in homes over an 8-week intervention phase to children with CP. Thirteen pediatric participants were recruited, ranging in age from 5 to 16 years. Reiki Therapy was administered by a Level 3 Reiki Therapist in the home for 8 consecutive weeks. Parents completed on-line questionnaires addressing their children's unpleasant symptoms. Hair cortisol was measured as an indicator of stress. Nearly all study procedures were completed by the participants, indicating that the methods are feasible for a larger study. Reiki Therapy significantly decreased pain while lying down (3.09 vs. 2.00; p = .002) but not while sitting (2.55 vs. 2.09; p = .40). Anger symptoms showed a trend towards improvement in the participants. These preliminary findings demonstrate that Reiki is a therapeutic modality worthy of further investigation in the CP pediatric population. Highlights: Home-based Reiki Therapy was well tolerated in children with Cerebral Palsy. RT was well-received and associated with a decrease in some measures of pain with a trend toward improvement in other symptoms. Further studies are needed to evaluate RT in populations of children with Cerebral Palsy and other chronic conditions.